Carleman estimate for the Navier–Stokes equations and applications. (1st August 2022) - Imanuvilov, Oleg Y; Lorenzi, Luca; Yamamoto, Masahiro
Abstract: For linearized Navier–Stokes equations, we first derive a Carleman estimate with a regular weight function. Then we apply it to establish conditional stability for the lateral Cauchy problem and finally we prove conditional stability estimates for the inverse source problem of determining a spatially varying divergence-free factor of a source term.